Hydrogeochemistry of groundwater from different aquifer in Lower Kelantan Basin, Kelantan, Malaysia - Sefie, Anuar; Aris, Ahmad Zaharin; Shamsuddin, Mohd Khairul Nizar; Tawnie, Ismail; Suratman, Saim; Idris, Azrul Normi; Saadudin, Syaiful Bahren; Wan Ahmad, Wan Kamaruzaman (Elsevier, 2015)
The groundwater geochemistry of Lower Kelantan Basin was evaluated based on major ions characteristic to determine its suitability for drinking, domestic use and irrigation. Groundwater samples from different aquifer layers (shallow, intermediate and deep) were collected and analysed for pH, electrical conductivity (EC), total dissolved solid (TDS), Ca, Mg, Na, K, Cl, SO4, CO3, HCO3, NO3, Fe and Mn. The results show that the shallow groundwater is dominated by Ca-HCO3 and Na-HCO3 while intermediate is dominated by Na-Cl and Na-HCO3, and deep aquifer by Na-HCO3 water facies. The sodium adsorption ratio (SAR) and salinity hazard indicate that the groundwater from shallow and deep aquifer is suitable for irrigation purposes, and part of intermediate aquifer is not suitable for crop irrigation. Groundwater from shallow and deep aquifer is regarded as fresh water and suitable for drinking, domestic and agricultural irrigation use while groundwater from intermediate aquifer is slightly brackish water particularly closed to coastal area.